Who is Tracking What and Why? A Process for Centralizing the Tracking of Patron Interactions. Issue 4 (18th May 2020) - Ozburn, Lindsay; Lundstrom, Kacy
Abstract: After identifying developing a culture of assessment as a strategic goal, Utah State University Libraries determined that the next step was to centralize its patron interaction tracking processes. Previous initiatives limited collection to specific library units, including using inconsistent data collection, storage, and reporting practices. A task force was charged with centralizing the processes for collecting all desk interactions, consultations, and instruction across the library. This paper details the process of platform selection, stakeholder input, form revision, marketing, and piloting the new workflow, including lessons learned, challenges, and next steps toward maintaining data collection consistency with staff and administrative buy-in.